Second-trimester postabortion care for ruptured membranes, fetal demise, and incomplete abortion. Issue 2 (May 2015) - Mark, Alice G.; Edelman, Alison; Borgatta, Lynn
Abstract: Background: Guidance for postabortion care (PAC) is established for the first trimester but limited in the second trimester. Objectives: To establish evidence-based recommendations for PAC in the second trimester. Search strategy: Medline, POPLINE, and the Cochrane Central Register of Controlled Trials were searched with terms related to second-trimester PAC, including fetal demise, ruptured membranes, and incomplete abortion. The reference lists of retrieved articles were also searched. Selection criteria: Clinical trials and comparative studies of women presenting in the second trimester (12–28 weeks) were included if more than 50% of participants met PAC criteria or if outcomes for PAC were analyzed separately. Data collection and analysis: Data were extracted from included studies. When interventions in at least two articles were comparable, a meta-analysis was performed. Main results: Overall, 17 studies of 1419 women met inclusion criteria. Misoprostol given vaginally, sublingually, or buccally was associated with shorter expulsion times than was oral misoprostol. Additionally, 200 μg of misoprostol was more effective than lower doses. Pretreatment with mifepristone decreased expulsion time. Misoprostol was more effective than oxytocin. Conclusion: Misoprostol with or without mifepristone is an effective treatment for second-trimester PAC. The minimum misoprostol dose is 200 μg vaginally, sublingually, or buccally every 6–12 hours.